2014
DOI: 10.2528/pierc14082703
|View full text |Cite
|
Sign up to set email alerts
|

A Broadband Omnidirectional Antenna Array for Base Station

Abstract: Abstract-A high gain wideband antenna array with an omnidirectional radiation pattern is presented for base station. The antenna array is composed of four elements and a circular four-way power divider. The proposed planar antenna element consists of four pairs of arc dipoles and a balun, which can achieve a better impedance match and a wider frequency range. Furthermore, the conductor ground of the power divider with a larger size than the element is placed under the four antennas, which can also enhance the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…There are three patches excited individually to cover the industrial, scientific and medical radio (ISM) band and UWB frequency of operation for the entire cellular bands. 15 Compared to the planar antennas, this 3D antenna maintains a high gain all over the frequency of operation. In Yu et al, 16 a wideband horizontally polarized antenna is demonstrated using closely coupled array of dipole.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three patches excited individually to cover the industrial, scientific and medical radio (ISM) band and UWB frequency of operation for the entire cellular bands. 15 Compared to the planar antennas, this 3D antenna maintains a high gain all over the frequency of operation. In Yu et al, 16 a wideband horizontally polarized antenna is demonstrated using closely coupled array of dipole.…”
Section: Introductionmentioning
confidence: 99%
“…A monopole antenna three‐layered structure is developed using the concept of a discone antenna. There are three patches excited individually to cover the industrial, scientific and medical radio (ISM) band and UWB frequency of operation for the entire cellular bands 15 . Compared to the planar antennas, this 3D antenna maintains a high gain all over the frequency of operation.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these methods have a weakness of narrow bandwidths (about 6%). The concept of rotating electric field method is applied to conventional slot dipoles in [6] and an antenna array in [7], but their relative bandwidths are 15.4% and 39.4%, respectively. In addition, some new techniques are employed in [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The microstrip antennas are good candidates for these applications due to their small size, easy installation and low cost. For WLAN applications and WiMAX systems, several design methods for omnidirectional antennas have been developed in [1][2][3][4][5]. The collinear dipole array (COA) is a well-known high-gain dipole antenna introduced in [6] based on Franklin idea.…”
Section: Introductionmentioning
confidence: 99%